Physiological and proteomic analyses of salt stress response in the halophyte Halogeton glomeratus - Wang, Juncheng (Plant Cell Environ, 2015)
Very little is known about the adaptation mechanism of Chenopodiaceae Halogeton glomeratus, a succulent annual halophyte, under saline conditions. In this study, we investigated the morphological and physiological adaptation mechanisms of seedlings exposed to different concentrations of NaCl treatment for 21 d. Our results revealed that H. glomeratus has a robust ability to tolerate salt; its optimal growth occurs under approximately 100 mm NaCl conditions. Salt crystals were deposited in water-storage tissue under saline conditions. We speculate that osmotic adjustment may be the primary mechanism of salt tolerance in H. glomeratus, which transports toxic ions such as sodium into specific salt-storage cells and compartmentalizes them in large vacuoles to maintain the water content of tissues and the succulence of the leaves. To investigate the molecular response mechanisms to salt stress in H. glomeratus, we conducted a comparative proteomic analysis of seedling leaves that had been exposed to 200 mm NaCl for 24 h, 72 h and 7 d. Forty-nine protein spots, exhibiting significant changes in abundance after stress, were identified using matrix-assisted laser desorption ionization tandem time-of-flight mass spectrometry (MALDI-TOF/TOF MS/MS) and similarity searches across EST database of H. glomeratus. These stress-responsive proteins were categorized into nine functional groups, such as photosynthesis, carbohydrate and energy metabolism, and stress and defence response.